Beyond Administration: Instructional Leadership Strategies of Principals in Managing Learning Guidance Programs in Islamic Schools - Ahmad Rofii (Program Studi Doktor Manajemen Pendidikan Islam, Universitas Islam Internasional Darullughah Wadda'wah, 2026)
This study explores principals’ instructional leadership strategies in managing learning guidance programs in Islamic schools. The study was motivated by the growing need for school leadership practices that extend beyond administrative functions and focus on instructional improvement, teacher development, and student support. Employing a qualitative case study approach, data were collected through semi-structured interviews, observations, and document analysis involving principals, teachers, and school members directly engaged in learning guidance activities. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña through data condensation, data display, and conclusion drawing. The findings reveal that principals implemented several strategic practices, including establishing instructional vision and direction, promoting collaborative leadership, conducting academic supervision, integrating digital innovation, applying adaptive leadership approaches, and strengthening school culture. These strategies contributed to improving the effectiveness and sustainability of learning guidance programs while fostering teacher engagement and institutional commitment. The findings further indicate that leadership in Islamic schools integrates instructional practices with ethical and institutional values, creating a more holistic approach to educational management. This study contributes to the growing discussion on instructional leadership by providing contextual insights into how principals manage learning guidance programs within Islamic educational institutions.